Polyphenolic HRMS Characterization, Contents and Antioxidant Activity of Curcuma longa Rhizomes from Costa Rica - María Isabel Quirós-Fallas; Felipe Vargas-Huertas; Silvia Quesada-Mora; Gabriela Azofeifa-Cordero; Krissia Wilhelm-Romero; Felipe Vásquez-Castro; Diego Alvarado-Corella; Andrés Sánchez-Kopper; Mirtha Navarro-Hoyos (MDPI AG, 2022)
Curcuma longa constitutes an important source of secondary metabolites that have been associated with multiple health benefits. For instance, curcumin, demethoxycurcumin and bisdemethoxycurcumin, have been found to perform important biological activities, such as anti-inflammatory, antioxidant, anticancer, antimicrobial, antihypertensive and anticoagulant. These promising results prompted this research to evaluate the polyphenols of C. longa rhizomes in Costa Rica. The present work reports a comprehensive study on the polyphenolic profile and the contents of the three main curcuminoids as well as the antioxidant activity of extracts from C. longa rhizomes (n = 12) produced in Costa Rica. Through UPLC-QTOF-ESI MS, a total of 33 polyphenols were identified, grouped in eight types of structures. In addition, our findings on the main curcuminoids using UPLC-DAD show all rhizomes complying with total curcuminoids (TC) content established by the United States Pharmacopeia (USP). At an individual level, samples NW-3 and NE-1 show the higher contents (118.7 and 125.0 mg/g dry material), representing more than twice the average values of the lowest samples. These samples also exhibit the highest Folin-Ciocalteu (FC) reducing capacity results as well as the best DPPH (IC50 15.21 and 16.07 µg extract/mL) and NO (IC50 between 52.5 and 54.3 µg extract/mL) antioxidant values. Further, Pearson correlation analysis findings indicated positive correlation (p < 0.05) between TC, CUR with FC results (r = 0.833 and r = 0.867 respectively) and negative correlation (p < 0.05) between CUR, TC and FC with DPPH results (r = −0.898, r = −0.911, and r = −0.890, respectively) and between NO results and DPPH (r = −0.805, p < 0.05). Finally, results for Principal Component Analysis (PCA) showed composition variability associated with their region of origin with products from the Northeastern (NE) region exhibiting higher average values for FC, TC and antioxidant activities. Further, PCA confirmed that two samples, namely NE-1 and NW-3, stand out by presenting the highest PC1 due to their particularly high TC, CUR and antioxidant activities. Consequently, our findings agree with previous results indicating the importance of C. longa extracts to elaborate products with potential benefits for health, while delivering extracts with higher levels of curcuminoids than previous reports and exhibiting high antioxidant activity.